God's provision, humanity's need : the gift of our dependence - McKirland, Christa L., 1985-; Torrance, Alan J. (Grand Rapids, MI, Baker Academic, 2022)
"Makes an exegetical and theological case that human beings were created to need the presence of God in order to flourish"--
"Foreword by Alan J. Torrance" -- from cover
Includes bibliographical references (pages 185-201) and indexes
Keywords: Trust in God -- Christianity; Dependency (Psychology) -- Religious aspects -- Christianity